2024
DOI: 10.1038/s41440-024-01605-x
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the effects of renal denervation at early or advanced stages of hypertension on cardiac, renal, and adipose tissue pathology in Dahl salt-sensitive rats

Kohzo Nagata,
Kaito Tagami,
Touko Okuzawa
et al.

Abstract: Renal denervation (RDN) has emerged as a novel therapy for drug-resistant hypertension. We here examined the effects of RDN at early versus advanced stages of hypertension on blood pressure and organ pathology in rats with salt-sensitive hypertension. Dahl salt-sensitive (DahlS) rats fed an 8% NaCl diet from 6 weeks of age were subjected to RDN (surgical ablation and application of 10% phenol in ethanol) or sham surgery at 7 (early stage) or 9 (advanced stage) weeks and were studied at 12 weeks. RDN at early o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 46 publications
1
2
0
Order By: Relevance
“…Therefore, it is often speculated that the organprotective effects of RDN may be associated with its sympathoinhibitory effect; however, this remains unclear because most clinical and animal studies have not evaluated sympathetic activity. Interestingly, the present study by Nagata et al demonstrated the cardiorenal protective effects of RDN without decreasing systemic sympathetic nerve activity [2]. We also demonstrated that RDN attenuated blood pressure elevation probably due to decreased activity of the circulating RAS by inhibition of efferent renal nerve activity, without decreasing sympathetic outflow in young stroke-prone spontaneously hypertensive rats [8].…”
supporting
confidence: 64%
See 2 more Smart Citations
“…Therefore, it is often speculated that the organprotective effects of RDN may be associated with its sympathoinhibitory effect; however, this remains unclear because most clinical and animal studies have not evaluated sympathetic activity. Interestingly, the present study by Nagata et al demonstrated the cardiorenal protective effects of RDN without decreasing systemic sympathetic nerve activity [2]. We also demonstrated that RDN attenuated blood pressure elevation probably due to decreased activity of the circulating RAS by inhibition of efferent renal nerve activity, without decreasing sympathetic outflow in young stroke-prone spontaneously hypertensive rats [8].…”
supporting
confidence: 64%
“…The present study by Nagata et al reported the effects of RDN at early versus advanced stages of hypertension on blood pressure elevation and organ pathology, including kidney, heart, and adipose tissue, in Dahl salt-hypertensive rats fed 8% NaCl diet from 6 weeks of age [2]. The authors demonstrated that RDN at early stage (7 weeks of age) or advanced stage (9 weeks of age) attenuated blood pressure elevation.…”
mentioning
confidence: 54%
See 1 more Smart Citation